Nirmali Seed as a Natural Biosorbent; Evaluation of its Potential for Iron (II) Removal from Steel Plant Effluents and Sewage Disinfecting Capacity - Maruthi, Y. Avasn; Dadhich, Anima S.; Hossain, Kaizar; Jyothsna, A. (European Journal of Sustainable Development, 2013)
The idea of water clarification by natural coagulants is many centuries old. Naturalcoagulants like Moring oelifera, Mangifera indica and Prunusarmeniaca,Strychnospotatorum are used for the treatment of waste waters. Nirmali Seed is a naturalcoagulant material with polyelectrolytes. These polyelectrolytes are responsible forcoagulation property of Nirmali seeds. In general, the studies rampant in the literaturereported application of Nirmali seed powder as water extract or as powder with doseselection using jar test. The treatment in most of the cases is based upon coagulation andremoval. But in this study it has been modified that the methodology to suit our objectivesas wanted to test the potential of Nirmali seed as a solid bio-sorbent surface in solidsolution equilibrium adsorption studies. The dose selection has been done keeping in mindthe amount of polyelectrolyte released when the seed powder is left in solution. Theproperty of physi-sorption aided with chemi-sorption with minimum dose has been givenimportance in the present study.The chief goal of this study is to find out the feasibility of applications of Nirmali Seedsfor both Iron (II) reduction as well as disinfecting agent for sewage samples.